Penglipuran village’s cultural traditions and local wisdom shaping a distinctive, sustainable tourist destination in highland Bali - Ni Komang Ayu Sumartini; I Ketut Santra; I Made Sumartana; Ni Wayan Sadiyani; Majid Wajdi; Dr. Sneha Chaurasiya; Hauwa Sani Ahmad (Yayasan Mitra Persada Nusantara, 2026)
Penglipuran Village, located in Bali, has become one of the famous tourist destinations thanks to its uniqueness in maintaining traditional culture and architecture. The purpose of writing this paper is to dig deeper into the attractiveness of Penglipuran Village as a tourist destination, as well as to understand the factors that make it special compared to other tourist villages in Bali. The research methods used in this paper include literature studies from various sources, such as scientific articles, tourism journals, and official websites that examine the development of Penglipuran Village as a tourist destination. In addition, data is also collected through observation and analysis of tourist visit reports. The discussion in this paper includes the history and development of Penglipuran Village, village management in maintaining cultural preservation, and the impact of tourism on the local community. The analysis shows that the uniqueness of traditional architecture, clean environment, and strong traditional values are the main attractions that maintain the popularity of this village as an authentic tourist destination. The conclusion of this paper is that Penglipuran Village has succeeded in combining tourism with the preservation of local culture, so that it becomes a model that is worthy of imitation in the development of other tourist villages in Indonesia. The preservation of tradition and the commitment of the local community in maintaining the beauty of the village is the key to the success of this village as a leading tourist destination.